Guardians of language twenty voices through history - Coulmas, Florian (Oxford Oxford University Press, 2016)
This book provides an accessible account of the origins and conceptual foundations of language policy. Florian Coulmas discusses the influence of twenty intellectuals from medieval to modern times, and from a variety of cultures, who have taken issue with language, its use, development, and political potential. These 'guardians of language' range from renowned figures such as Dante, Noah Webster, and Gandhi, to less well-known individuals such as the Spanish grammarian Antonio de Nebrija and Senegalese politician and poet Leopold Sedar Senghor. Each chapter begins by providing background information on the scholar whose work is being reviewed and ends with a summary of his key thoughts on language in the form of an imaginary interview.
Includes bibliographical references (pages 309-334) and indexes.
Keywords: Language policy